Acute Hepatitis Induced by Lyprinol, the Lipid Extract of the Green-Lipped Mussel (Perna canaliculus), in a Patient with Polyarthrosis - Amr Abdulazim; Marion Hädrich; Matteo Montani; Nasser Semmo (Case Reports in Hepatology)
Lyprinol, the lipid extract of the green-lipped mussel (Perna canaliculus), is a readily and freely available agent with a putative anti-inflammatory impact. It has already found application as a complementary and supplementary treatment of osteoarthritis, rheumatoid arthritis, asthma, and cancer. So far no major side effects for Lyprinol have been reported, yet. Here, we present the case of a 76-year-old woman with acutely exacerbating abdominal pain and highly elevated liver transaminases while taking Lyprinol as a complementary treatment of polyarthrosis.